L'abus de pouvoirs du mandataire en droit civil québécois - Fabien, Claude (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
The purpose of this article is to study the rules governing the phenomenon of mandatories abusing their powers, under Quebec Civil Code. It also reviews the rules proposed by the Civil Code Revision Office in its 1971 and 1976 Reports on the contract of Mandate and in its 1976 Report on administration of property of others. It shows that on many issues the Office has chosen a rather conservative approach and decided to stick to time-proven rules. It also flags the areas where the Office advocates new rules, with appropriate comments. The article is divided in two parts, the first one dealing with the scope of abuse of powers, the second with its effects. Part one asks « When does a mandatory abuse his powers ? » and answers by distinguishing between the wrongful exercise of mandatory's actual powers and the exercise, right or wrong, of non-existant powers. Part two then asks « What are the effects of abuses of powers ? » and deals on one hand with the liability towards third parties of both mandators and mandatories, and on the other hand with the liability of mandatories towards their mandators. The interest of part one lies mainly with the distinction it makes between two types of abuses of powers and with the analysis of the remarkable contribution of the Report on administration of the property of others into the field of Mandate. Part two derives its interest from the study of rules aimed at protecting third parties against abuses of powers of mandatories, and from testing the relevance of distinguishing between two types of abuses of powers. One conclusion, among others, emerges from this article. Mandators are fully liable towards third parties when mandatories abuse their powers by using them wrongfully. Conversely mandators are not liable when mandatories abuse their powers by using non-existant powers, although this principle suffers exceptions numerous enough to constitute a genuine regime of protections for third parties against self-empowered mandatories. The article suggests however that Quebec Law could go one step further by improving protection of third parties under the existing notion of apparent mandate, especially for those dealing with companies.